Modulation of benzylisoquinoline alkaloid biosynthesis by overexpression berberine bridge enzyme in Macleaya cordata. Issue 1 (December 2018) - Huang, Peng; Liu, Wei; Xu, Min; Jiang, Ruolan; Xia, Liqiong; Wang, Peng; Li, Han; Tang, Zhaoshan; Zheng, Qiyin; Zeng, Jianguo
Abstract Macleaya cordata produces a variety of benzylisoquinoline alkaloids (BIAs), such as sanguinarine, protopine, and berberine, which are potential anticancer drugs and natural growth promoters. The genes encoding the berberine bridge enzyme (BBE) were isolated fromM. cordata andPapaver somniferum, and then the two genes were overexpressed inM. cordata . Through liquid chromatography with triple-quadrupole mass spectrometry analysis, it was determined that McBBE-OX caused higher levels of (S )-norcoclaurine, (S )-coclaurine, (S )-N -cis-methylcoclaurine, (S )-reticuline, (S )-tetrahydrocolumbamine, (S )-tetrahydroberberine, (S )-cheilanthifoline, and (S )-scoulerine than PsBBE-OX, empty vector or control treatments. qRT-PCR analysis demonstrated that the introduced genes in the transgenic lines were all highly expressed. However, the levels of sanguinarine (SAN) and chelerythrine (CHE) in all the transgenic lines were slightly lower than those in the wild-type lines, possibly because the overexpression ofMcBBE causes feedback-inhibition. This is the first report on the overexpression of potential key genes inM. cordata, and the findings are important for the design of metabolic engineering strategies that target BIAs biosynthesis.